Economic and social benefits of socially responsible actions towards employees in agribusiness enterprises - Matejun Marek; Ratajczak Marcin (Management, 2019)
The aim of the paper is to identify the scope of socially responsible actions towards employees in agribusiness enterprises and to assess their impact on the level of economic and social benefits resulting from the use of the CSR concept in business practice. The survey research carried out on a sample of 325 companies from the SME sector conducting business in rural areas of the Mazowieckie Voivodeship served to meet the objective of the paper. The results indicate a positive, strong impact of involvement in the CSR activities on the obtained effects, which is more pronounced in the case of economic benefits than social benefits, and can be observed more clearly in smaller companies. Key socially responsible actions towards employees include employee satisfaction surveys as well as data protection and protection of employee privacy. Activity in the analyzed CSR area mainly translates into financial performance and building a positive image of enterprises in their environment